Localização e orientação dos quimiorreceptores de CO2 e/ou pH envolvidos no controle dos reflexos cardio-respiratórios e da respiração aérea em jeju, Hoplerythrinus unitaeniatus (Teleostei, Erythrinidae) - Boijink, Cheila de Lima (2004)
In the present study we determined the location and orientation of the CO2 and/or pH chemoreceptors and analyzed the cardio-respiratory responses and the aerial respiration in jeju (Hoplerythrinus unitaeniatus) during graded hypercarbia (1, 2.5, 5, 10 e 20% de CO2) and acid medium (pH ~ 7, 6.0, 5.8, 5.6, 5.3 e 4.7) (1, 2, 3, 4 e 5 mM de HCl). The chemoreceptors orientation was determined by means of a series of injections of different hypercarbic solutions (5, 10 e 20% de CO2) in the caudal vein (internal) and buccal cavity (external). To distinguish the orientation of the CO2 and H+ chemoreceptors, acid solutions (HCl) at same pH of the internal (pH 5.1, 4.9, and 3.7) and external (pH 5.6, 5.3, and 4.7) solutions were applied, and significant responses in relation to the control values were not recorded. In another group of fish previously tested acid solutions (30, 40, and 50 mM HCl) were injected. This injections caused a decrease in the extra-cellular blood pH to levels similar to those found during the injections of internal and external hypercarbic solutions. The location of the chemoreceptors was determined by bilateral denervation of branches of the cranial nerves IX (glossopharyngeal) and X (vagus) to the gills. The heart rate, arterial blood pressure, respiratory frequency and ventilation amplitude were recorded for intact and denervated fish. The data indicated that the CO2/pH chemoreceptors eliciting the cardio-respiratory responses to hypercarbia are exclusively branchial and are externally oriented. Jeju respond to hypercarbia of 5% CO2 with bradycardia, hypertension and increases in the ventilatory frequency and ventilation amplitude. Concentrations higher than 5% caused anesthetic effect. The cardiac responses are mediated by CO2/pH chemoreceptors distributed in all gill arches, while the respiratory responses are mediated by chemoreceptors located in the 1st gill arch. Furthermore, hypercarbia also induced aerial respiration in intact fish and in those with the 1st gill arch denervated. The denervation of the four gill arches did not abolish completely the aerial respiration, suggesting that chemoreceptors involved in this response are located in extra-branchial sites. The changes in the internal and external H+ concentrations or in the water did not affect the cardiorespiratory responses and aerial respiration frequency, unless if accompanied by hypercarbia.